Combining amphibious geomorphology with subsurface geophysical and geological data: A neotectonic study at the front of the Alps (Bernese Alps, Switzerland). (7th September 2017) - Fabbri, S.C.; Herwegh, M.; Horstmeyer, H.; Hilbe, M.; Hübscher, C.; Merz, K.; Schlunegger, F.; Schmelzbach, C.; Weiss, B.; Anselmetti, F.S.
Abstract: In the vicinity of Lake Thun at the front of the Bernese Alps (Switzerland), we performed a multidisciplinary neotectonic study combining onshore and offshore geological data and geophysical measurements in order to identify potentially active fault structures. Paleoseismic reconstructions on the northern margin of the Alps have documented several strong earthquakes with moment magnitudes ≥6 during the Late Quaternary, which have long recurrence intervals of 1, 000 to 2, 000 years. Such earthquakes are expected to produce surface ruptures. In this light, we investigated the study area located near Lake Thun primarily for on-fault evidence, to date still a shortcoming in Switzerland. We detected several features indicating potential fault activity, such as aligned subaquatic morphological depressions, offset horizons observed in reflection seismic profiles of lake sediments and in ground-penetrating radar images, all delineating a fault trace. Observations of fluvial deposits in a nearby gravel pit in the prolongation of the inferred structure supports these findings. A narrow zone with rotated long axes of pebbles (inclining at ∼60°) is clearly distinguishable and crosscuts the original bedding with predominantly horizontal orientation of pebble axes. This zone further shows an apparent 1.1 m offset of oxidized horizons and is therefore considered as a potential fault plane in a normal faulting regime. A dated radiocarbon age of ∼11, 000 years BP of the gravel deposits hence suggests a younger fault activity during the Holocene. The Einigen Fault Zone (EFZ), proposed on the basis of these observations, is considered as a complex fault system with a combination of dextral strike-slip and normal faulting, as suggested by GPR images. Observations in the gravel pit and radar data independently show that it includes at least two fault strands. However, while five earthquakes with epicentral intensities I0  ≥ VI and numerous smaller seismic events are known within less than 30 km epicentral distance to Lake Thun over the past 400 years, none of these seem to coincide with the location of the EFZ.